Budget Politics In The Public Eye: A Critical Study Of Budget Cut Policies : Public Perception of Government Budget Cut Policy in Pekalongan City - Dea Syakiroh Maghfirotun Nisa', Dea (Universitas Negeri Surabaya, 2025)
The government's budget-cutting approach, particularly in public services such as education, health, and social protection, has elicited a variety of opinions from the populace. The research intends to analyse the impact of the budget cut policy from the standpoint of budgetary policy and to uncover how the people of Pekalongan City perceive it. The study uses a qualitative approach through in-depth interviews with various community groups, including teachers, students, private employees, housewives, and government officials. In-depth interviews were conducted utilising semi-structured guidelines and voice recording equipment, with secondary sources such as government regulations and budget reports to supplement the data. Data analysis was carried out using a thematic process based on Creswell's analysis model, which included coding and the creation of major themes.The results show that there are significant differences in perceptions between community groups, influenced by social background, level of dependence on public services, and level of trust in the government. Directly affected groups tend to be critical and concerned about the decline in service quality, while other groups are more understanding of the government's fiscal efficiency rationale. This research highlights the importance of transparency, effective communication and public participation in the policy-making process to ensure that budget cuts are accepted and have a positive impact on society. It is crucial to develop fiscal policies that are both technically and socially efficient, according to the study's implications.